2019 9th International IEEE/EMBS Conference on Neural Engineering (NER) 2019
DOI: 10.1109/ner.2019.8717043
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Multi-task Inverse Covariance Estimation for Connectivity Analysis in EEG Source Space

Abstract: Understanding how different brain areas interact to generate complex behavior is a primary goal of neuroscience research. One approach, functional connectivity analysis, aims to characterize the connectivity patterns within brain networks. In this paper, we address the problem of discriminative connectivity, i.e. determining the differences in network structure under different experimental conditions. We introduce a novel model called Sparse Multi-task Inverse Covariance Estimation (SMICE) which is capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The study of ESI is of great significance in both neuroscience and clinical applications ( Congedo and Sherlin, 2011 ). Accurate estimation of brain sources can not only help neuroscientists to better understand the brain mechanism ( Liu et al, 2019 ) and the pathological characteristics of brain injury or mental disorders ( da Silva, 2013 ), but also help doctors to identify the lesion areas of brain diseases such as epilepsy focal regions, which can contribute to the improvement of the accuracy of presurgical evaluations ( Sanei and Chambers, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of ESI is of great significance in both neuroscience and clinical applications ( Congedo and Sherlin, 2011 ). Accurate estimation of brain sources can not only help neuroscientists to better understand the brain mechanism ( Liu et al, 2019 ) and the pathological characteristics of brain injury or mental disorders ( da Silva, 2013 ), but also help doctors to identify the lesion areas of brain diseases such as epilepsy focal regions, which can contribute to the improvement of the accuracy of presurgical evaluations ( Sanei and Chambers, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Die Verbindung zwischen Narkosetiefe, Bewusstheit, Erinnerungsbildung und EEG-Signalanalyse ist durch heutige DoA-Monitoring-Verfahren noch nicht hergestellt. Allerdings gibt es faszinierende Untersuchungen, die möglicherweise den Zusammenhang zwischen Bewusstsein und Anästhesietiefe durch Musterveränderung im EEG darstellen können [8,44,45,46].…”
Section: Klassifikation Intraoperativerunclassified
“…This is primarily because the correlation matrix can depict the interactions and cooperative activities among different brain regions (Liu and Ye, 2023 ). It has been demonstrated that due to the non-uniform connectivity patterns in the brain, the correlation matrix of EEG signals is typically sparse (Liu et al, 2019 ). For example, Figure 1 exemplifies the correlation matrix of 62 EEG channels utilized in a fatigue detection task with a classification accuracy of 94%.…”
Section: Introductionmentioning
confidence: 99%